The Effect of Work-Life Balance and Compensation on Employee Performance Through Job Satisfaction as an Intervening Variable - Gunawan, Egit Fahri; Sudarmiatin, Sudarmiatin; Churiyah, Madziatul (IJBLE Scientific Publications Community Inc., 2024)
This study aims to determine and analyze whether there is an influence of work-life balance and compensation on employee performance with job satisfaction as an intervening variable in employees of PT Indominco Mandiri, East Kalimantan. This research is a quantitative study with descriptive and explanatory research methods. The population in this study were employees at PT Indominco Mandiri, East Kalimantan, totaling 230 people while the research sample was obtained as many as 145 people. Data collection techniques in this study were questionnaires, interviews, and observations. Data analysis techniques using associative and quantitative approaches with SmartPLS shower. The results showed that work-life balance has a negative and insignificant effect on the employee performance of PT Indominco Mandiri. Compensation has a positive and significant effect on the employee performance of PT Indominco Mandiri. Work-life balance has a positive and significant effect on the job satisfaction of PT Indominco Mandiri employees. Compensation has a positive and significant effect on the job satisfaction of PT Indominco Mandiri employees. Job satisfaction has a positive and significant effect on the employee performance of PT Indominco Mandiri. Work-life balance indirectly through job satisfaction as an intervening variable has a positive and significant effect on employee performance of PT. Indominco Mandiri. Compensation indirectly through job satisfaction as an intervening variable has a positive and significant effect on the employee performance of PT Indominco Mandiri